TYPES OF STEM CUTTINGS AND ENVIRONMENTS ON THE GROWTH OF COFFEE STEM SHOOTS - REZENDE, Tiago Teruel; BALIZA, Danielle Pereira; OLIVEIRA, Diego Humberto de; CARVALHO, Samuel Pereira de; ÁVILA, Fabrício William; PASSOS, Alexandre Martins Abdão dos; GUIMARÃES, Rubens José (Scientia Agraria, 2010)
Looking to contribute to the formation of an appropriate methodology for Coffea arabica L. stem shoots production through vegetative propagation, this work aimed to evaluate the effect of different types of stem cuttings used for the formation of Arabic coffee stem shoots obtained from stem cuttings, under two different environments. The experiment was carried out in an completely random design, in a 3 x 2 factorial experiment, corresponding to three types of segments (herbaceous, semi-woody and woody) and two environments (shaded nursery and greenhouse). The experiment was conducted for 90 days. At conclusion the following variables were evaluated: plant height, number of nodes, number of leaf pairs, length of the principal root and the plant dry matter. It was observed that for the longest root of the semi-woody cutting presented the highest average, differing significantly from the other cuttings. For total dry matter, the semi-woody and woody cuttings did not present significant difference amongst themselves, but they were superior to the herbaceous cuttings. The shaded nursery stood out as the best local for the development of these seedlings.